An Experimental Study of Paclitaxel Embolisation During Drug Coated Balloon Angioplasty. (April 2019) - Boitet, Auréline; Grassin-Delyle, Stanislas; Louedec, Liliane; Dupont, Sebastien; Lamy, Elodie; Coggia, Marc; Michel, Jean-Baptiste; Coscas, Raphaël
Abstract : Objective: Drug coated balloons (DCB) improve the patency of femoropopliteal angioplasty but their use in infrapopliteal lesions is debateable as paclitaxel (PTX) particle embolisation has been suspected in some trials. The aim of this study was to compare experimentally five DCBs in terms of distal embolism of PTX. Methods: Twenty-five New Zealand rabbits were divided into five groups according to the DCB used: Lutonix (Bard), In.Pact (Medtronic), Passeo-18 Lux (Biotronik), Ranger (Boston Scientific), and Stellarex (Spectranetics) ( n  = 5 in each group). After ligation of the right common iliac artery, a 4 × 40 mm DCB was inflated in the infrarenal aorta for 180 seconds. Rabbits were euthanised two hours after inflation of the DCB. The infrarenal aorta, a blood sample and three left hind leg muscles (tensor fasciae latae [TFL], vastus lateralis [VL], and tibialis anterior [TA] muscles) were harvested for blind measurement of PTX concentrations and histological analysis (PTX emboli count). Results: In the TA muscle (the most distal), concentrations of PTX were significantly lower for the Ranger (0.067 ng/mg) than for the Lutonix (0.342 ng/mg; p  = .008), In.Pact (0.370 ng/mg; p  = .012), and Passeo-18-Lux (0.160 ng/mg; p  = .021) DCBs. Similarly, concentrations of PTX were significantly lower for the Passeo-18-Lux than for the In.Pact ( p  = .028). Concentrations of PTX were not significantly different between DCBs in the TFL and VL muscles. Concentrations of PTX were found to be significantly higher in the plasma and lower in the aorta and on the DCBs after use of Lutonix compared with the four other DCBs. Histological analysis revealed evidence of embolised PTX crystals in small arterioles of all muscle tissue samples without any significant difference between the DCBs. Conclusions: This study suggests some differences regarding distal embolisation profiles between the five assessed DCBs. Although clinical implications remain to be demonstrated, the present results may have implications when choosing a DCB, especially in a critical limb ischaemia setting.